Trial protocol for the validation of the ‘Toronto Aortic Stenosis Quality of Life (TASQ) Questionnaire’ in patients undergoing surgical aortic valve replacement (SAVR) or transfemoral (TF) transcatheter aortic valve implantation (TAVI): the TASQ registry - Peter Bramlage; Derk Frank; Simon Kennon; Nikolaos Bonaros; Mauro Romano; Thierry Lefèvre; Carlo Di Mario; Pierluigi Stefàno; Flavio Luciano Ribichini; Dominique Himbert; Marina Urena-Alcazar; Jorge Salgado-Fernandez; et al. (Open Heart)
Background Patients with severe aortic stenosis (AS) have a reduced life expectancy and quality of life (QoL), owing to advanced age and the presence of multiple comorbidities. Currently, there is no AS-specific QoL measurement tool, which prevents an accurate assessment of how this chronic condition and its treatment affect patients. The Toronto Aortic Stenosis Quality of Life Questionnaire (TASQ) was developed in order to address this deficiency.Methods The present trial protocol was designed to enable validation of the TASQ, which has been produced in five languages (English, French, German, Italian and Spanish) to increase usability. Patients with severe AS who are undergoing surgical aortic valve replacement (SAVR) or transcatheter aortic valve implantation (TAVI) will be asked to complete the TASQ and, for comparative purposes, the Kansas City Cardiomyopathy Questionnaire and the general health-related QoL Short Form-12 questionnaire. The questionnaires will be completed prior to the intervention, at discharge, as well as at 30 days and 3 months follow-up. A total of 290 patients will be recruited across one Canadian and nine European centres. Overall, the protocol validation aims to include 120 patients undergoing transfemoral TAVI (TF-TAVI), 120 undergoing SAVR and up to 50 being treated medically. The primary objective of the registry is to validate the TASQ in five different languages. The secondary objective is to assess the utility of the TASQ for assessing differences in QoL outcome between patients undergoing TF-TAVI, SAVR or medical management for their AS.Discussion Validation and roll-out of the TASQ will enable clinicians to capture an accurate assessment of how AS and its management affects the QoL of patients and will help them to determine the most appropriate treatment strategy for individual patients.Trial registration number NCT03186339